The Influence of Sarcasm on Communication Misunderstandings in University Students - Suwendri, Risti Ayu; Manggalani, Rina; Ajat, Ajat; Gautama, Sidartha Adi; Aryanti, Nina Yudha (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
This study aims to determine the effect of the use of sarcasm on communication misunderstandings in college students. Sarcasm is a form of communication that contains satire or irony, and often causes ambiguity of meaning, so it has the potential to cause misunderstanding in the communication process. This research uses a quantitative approach with an ex-post facto method. The research subjects were students of the Buddhist Communication Science Study Program of STIAB Jinarakkhita Lampung TA. 2024-2025 as many as 49 respondents. Data were collected through questionnaires, then analyzed using normality test, homogeneity test, and simple linear regression analysis with the help of SPSS 16.0. The results showed that sarcasm had a significant effect on communication misunderstanding, with a coefficient of determination (R Square) of 0.487 or 48.7%. This means that 48.7% of students' communication misunderstanding is influenced by the use of sarcasm. This finding shows that the higher the intensity of sarcasm use, the greater the potential for communication misunderstanding. Therefore, it is important for students to pay more attention to the way they communicate so that the messages conveyed do not cause the wrong interpretation.